Genome size determination of cucumber (cucumis sativus), honeydew (cucumis melo inodorus) and rock Melon (cucumis melo cantalupensis) via flow cytometry - Yumni, Raden Muhamad Imaduddin; Karim, Mohd Fauzihan; Midin, Mohd Razik (Zibeline International Publishing, 2021)
The family of Cucurbitaceae consists of species with economical and nutritional value. Morphologically, there are only few differences between Cucumis species. The interspecific and intraspecific variation in the genome size of the Cucumis species are not discovered yet. Due to this, this study aims to determine the genome size of C. sativus, C. melo inodorus and C. melo cantalupensis using flow cytometry (FCM) method. Nuclei suspension of selected Cucumis species were extracted using LBO1 lysis buffer by manual chopping technique and stained by propidium iodide priot to FCM analysis. Genome size of C. sativus, C. melo inodorus (Honeydew) and C. melo cantalupensis (Rockmelon) were determined by using Glycine max (Soybean) as an external reference standard (2C = 2.5 pg). This study found that the genome size of C. sativus, C. melo inodorus and C. melo cantalupensis estimated to be 2.83 pg, 3.00 pg and 3.47 pg respectively. The genome size data obtained from this study can be used in future genome studies as well as species characterization.